Genotipificación de mutaciones frecuentes en pacientes con hipoacusia no sindrómica - Pace, Mariela Vanina (2023)
Hearing loss is the most common sensorineural disorder and congenital defect in developed countries, affecting 5% of the global population. The purpose of this study is to establish the presence of the most frequent variants in GJB2 and GJB6 genes in patients with non-syndromic hearing loss. In those who are heterozygous, the study will be broadened by analyzing non-frequent variants in GJB6 gene and in splicing sites of GJB2 gene. Fifty samples are analyzed from patients referred from several Otolaryngology, Genetics and Phonoaudiology Services and samples from the laboratory's archives, resulting in a total of 84 samples studied. Several molecular biology methodologies are used, such as Sequencing-PCR, GAP-PCR and RFLP-PCR.\nPathogenic variants in both alleles are detected in 12 of the 84 samples studied (14%), heterozygous genotypes are identified in 47 (56%), while 25 left remain undiagnosed (30%). Variant c.35delG in GJB2 gene resulted the most frequent mutated allele in the diagnosed patients, representing 58%, followed by variants in GJB2 gene c.59T>C p.Ile20Thr and c.101T>C p.Met34Thr (8% each). The remaining variants are 4% each. In conclusion, the techniques used show that 12 patients out of the 84 studied with non-syndromic hearing loss present pathogenic variants in genes that codify proteins of inner ear expression. The initial screening for variants in GJB2 and GJB6 genes is a suitable practice with excellent diagnostic yields.